Developing Android Based My Science App Learning Media with a SETS Approach on The Topic of the Solar System in Elementary Schools - Sari, Fita Permata; Budhiman, Arief; Prasetyo, Herry (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
This study aimed to develop an android-based My Science App learning media with the Science, Environment, Technology, and Society (SETS) approach for elementary school students on the solar system. The subject in this study were 23 sixth-grade students of SD Negeri Salebu 03 Majenang. This type of research is Research and Development. The initial stage of the study was observing the learning media used in learning, then developing the design and producing the android-based My Science App learning media with the SETS approach. The resulting learning media can help students understand learning material. The results of the feasibility assessment of learning media by media experts obtained 93.75% with very feasible criteria, and the evaluation by content experts got 96.25% with very feasible criteria. This research produces appropriate learning media for solar system topics.